2010
DOI: 10.1177/193229681000400624
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Total Analytical Error in Consumer and Hospital Glucose Meters Contributed by Hematocrit, Maltose, and Ascorbate

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…Lyon, et al15 reported that ascorbic acid produced statistically significant analytical errors with SMBG devices. These interferences may mask true hypoglycemia or hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Lyon, et al15 reported that ascorbic acid produced statistically significant analytical errors with SMBG devices. These interferences may mask true hypoglycemia or hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of these handheld blood glucose meters in critically ill patients has recently been questioned [21]. Many drugs, depending on the enzymatic reaction, may interfere with the blood glucose measurement (eg, ascorbic acid, acetaminophen, icodextrin) [22]. The main culprit in the accuracy of the blood glucose meters during critical illness appears to be anemia [23], which is widely tolerated in critically ill patients due to restrictive transfusion policies [24,25].…”
Section: Is Nice-sugar Evidence Against Blood Glucose Control?mentioning
confidence: 99%
“…Fundamental assumptions of this methodologic approach are that the measured value for blood [gluc] is minimally affected by changes in hematocrit (Hct) and sample temperature. Changes in Hct have been widely documented to influence the measured value for blood [gluc] when used to analyze human blood . It has been known for more than 100 years that intra‐erythrocyte [gluc] is lower than plasma [gluc] in cattle, horses, pigs, and dogs, but not in humans and other primates .…”
Section: Introductionmentioning
confidence: 99%